“Remédio anti-covardia” : cartografia de vulnerabilidades, comunicação e política na construção e performatividade do dia de luta antimanicomial - Lucas Henrique Nigri Veloso (2020)
The dissertation carried out a cartographic investigation about the interactional, communicational and political processes of production and performance of the protest “anti- asylum struggle day”, as constructed by the anti-asylum social movement in the city of Belo Horizonte, in the year 2019. We sought to verify and analyze, based on “tracks-wastes” generated-collected in deliberative processes and other events related to the research phenomenon, empirical evidence that indicates, on the one hand, the challenges that subjects and subjects crossed by intense social precariousness, such as those in situations of mental suffering,face to exercise their constitutional right of assembly, demonstration and democratic political claim in urban space. Concomitantly, we sought to learn from these same subjects about the conditions in which embodied social vulnerabilities can be reconfigured in order to become potentializing vectors for communicative, artistic, political and citizen agencies and practices. In other words, the dissertation sought to empirically testify how more vulnerable and precarious bodies than others could compose a grammar and performative framework that seeks to both denouncing injustices and the dismantling of public policies and institutions of mental health care and attention, as to put in check, displace and even devalue negative stigmas and labels that tend to reiterate situations of forgetfulness, abandonment and social precariousness. By making a theoretical pact with the philosophical framework of Judith Butler and other researchers, as well as an ethnographic pact with the subjects and subjects of research, it was intended to map the anti-asylum “imaginary” and “care poetics”, as constructed and expressed over the period and trajectory of the research carried out, aiming at (re)fictionalize sociological, political and existential points of view, knowledge and epistemes of the anti-asylum struggle in Minas Gerais. By placing the results generated in dialogue with the academic field, it is expected to contribute, among other things, to the perpetual review that the social sciences must carry out on themselves in order to better understand and intervene in the social worlds that are the object of their reflection, especially from the theories, experiences and meanings that research subjects have about their own social situation, vulnerabilities and political-existential potentialities.